2013
DOI: 10.1378/chest.13-0056
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs Toward Lung Cancer Screening Among US Veterans

Abstract: Background: Lung cancer (LC) is the leading cause of cancer-related death for veterans cared for by the US Veterans Health Administration. The LC burden among veterans is almost double that of the general population. Before implementation of an LC screening program, we set out to assess the role of beliefs and attitudes toward LC screening among veterans. Methods: Veterans presenting to the Ralph H. Johnson VA Medical Center were invited to complete a self-administered survey. The survey comprised questions ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 15 publications
3
50
0
Order By: Relevance
“…Individuals who perceive LDCT screening more favorably may have been more likely to participate than those apathetic to this issue, resulting in overestimates of enthusiasm for LDCT screening. However, the enthusiasm our respondents expressed for lung cancer screening is similar to that observed in prior primary care provider and patient surveys (9,10). Second, responses to hypothetical vignettes may not reflect actual screening behavior.…”
Section: Discussionmentioning
confidence: 57%
“…Individuals who perceive LDCT screening more favorably may have been more likely to participate than those apathetic to this issue, resulting in overestimates of enthusiasm for LDCT screening. However, the enthusiasm our respondents expressed for lung cancer screening is similar to that observed in prior primary care provider and patient surveys (9,10). Second, responses to hypothetical vignettes may not reflect actual screening behavior.…”
Section: Discussionmentioning
confidence: 57%
“…Tanner and colleagues 5 found that virtually all (93%) of their survey respondents would accept CT scan screening for lung cancer, a somewhat surprising result in light of prior surveys of attitudes toward screening among smokers. 6 , 7 There is potential for bias in the design and administration of this survey, however, and as such, there are reasons to be cautious before concluding that CT scan screening for lung cancer would be so widely accepted.…”
Section: Framing Discussion About Ct Scan Screening For Lung Cancer mentioning
confidence: 96%
“…In this issue of CHEST (see page 1783), Tanner and colleagues 5 take an important step forward by examining veterans' perceptions of their personal risk of lung cancer, their attitudes toward CT scan screening, and their willingness to undergo surgery for lung cancer. These are all important issues because current and former smokers-the target demographic for lung cancer screening-tend to underestimate their risk of cancer and to be less receptive to both screening and surgery for lung cancer.…”
Section: Framing Discussion About Ct Scan Screening For Lung Cancer mentioning
confidence: 99%
See 1 more Smart Citation
“…These decisions are often complex given the potential tradeoffs between quality and duration of life. The advent of new technologies and a greater appreciation for patient-centered care expands these complexities, as in the case of recommendations for advance care planning in the routine management of chronic obstructive pulmonary disease (COPD) (8) and for low-dose computed tomography scanning of individuals with significant tobacco histories (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%